Penerapan Prinsip Syariah & BMC dalam UMKM pada Brand Moko Donuts Kota Parepare - Muh. Fiqri Alif Utama; Muh. Akram Iswan; Hera Basri; St. Aulia; Rezki Fani (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
This study examines the implementation of sharia principles in the business management of MSME MOKO Donuts in Parepare City and analyzes how these principles are integrated into its business model. Using a qualitative case study approach, data were collected through observation, in-depth interviews with the owner, employees, and customers, and documentation. The analysis is grounded in five core principles of Islamic business ethics: tawhid, justice, free will, responsibility, and truthfulness. The findings indicate that MOKO Donuts has consistently applied sharia principles across operational, human resource, financial, and service dimensions, including the use of Islamic financial institutions to avoid riba. This study contributes to the literature by demonstrating that the integration of sharia principles with a structured business model can support ethical governance, customer trust, and business sustainability in MSMEs.